Pendidikan Multikultural dalam Pembelajaran Sejarah: Kajian Teoritis, Filosofis, dan Strategi Aplikatif - Kurniawan, Dadan Adi; Astutik, Dwi (Universitas Galuh, 2025)
This study examines three main focuses, namely the nature and importance of multicultural education, the relationship between history learning and multicultural education, and the applicative strategy of multicultural education through history learning. This study uses a qualitative descriptive-analytical method. The data collection technique uses literature studies by utilizing various sources such as journals, books, magazines, and credible and relevant articles. This study uses a structural functional sociology approach and history as a framework for thinking as well as an analytical tool. The results of the study show that multicultural education is education that forms and fosters an egalitarian, appreciative, and tolerant culture amidst many differences and diversity. By exploring various examples of multiculturalism and multiculturalism crises in the past, students can use it as reflection material to knit, cultivate, and maintain diversity, nationalism, national identity, and character formation. The applicative strategy of multicultural education in history learning is carried out through the selection of strategic materials, design of models, methods, and learning approaches that train students to maintain unity, respect each other, and appreciate each other amidst many differences. With this research, it is expected to be a consideration for history teachers in developing paradigms, content and multicultural learning designs. In addition, it also becomes a constructive reference material for educational policy makers at the educational unit level (school) and at the central level.